PSYCHOLOGICAL CORRECTION OF PERSONALITY RESOCIALIZATION IN THE POSTPENITENTIARY PERIOD - Сорока, Анатолій Володимирович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
Psychological correction of person’s resocialization in the postpenitentiary period. The article studies the testing of individual results of the author’s program of psychological correction of personality resocialization in the postpenitentiary period in accordance with the implementation of the system-complex proposed by us [2–7]. The practical significance of the research is to test and validate the results of the research (confirmed by the implementation acts), namely: «Psychodiagnostic and psychocorrection programs for the study of readiness for resocialization of the individual after being released from serving the sentence» in the centers of social adaptation of the Kharkiv and Sumy regions of Ukraine. As a result of the work, there have been significant changes in a number of indicators of the system complex we are investigating, the severity of which at the time of completion of the study compared with its beginning allows us to assert that the process of resocialization of the subjects is successful. Eight of those who studied after participating in the program successfully married (material assistance provided to them by the relevant charitable and religious organizations of Ukraine) and happily living in the family, bringing up children. And the author as the head of the public organization of the North-East interregional department for the execution of punishments and probation of the Ministry of justice of Ukraine in every possible way tries to provide them with any assistance. The results of the study are used in the practical work of psychologists of penitentiary institutions, probation of the above-mentioned areas, as well as during training in the system of professional training and professional development of psychologists of penitentiary institutions, probation of Ukraine.